In Vitro Starch Digestibility and Expected Glycemic Index of Kodo Millet (Paspalum scrobiculatum) as Affected by Starch–Protein–Lipid Interactions. Issue 3 (7th May 2013) - Annor, George Amponsah; Marcone, Massimo; Bertoft, Eric; Seetharaman, Koushik
ABSTRACT: The effect of starch–protein–lipid interaction on the in vitro starch digestibility and expected glycemic index (eGI) of kodo millet flour (MF) was investigated. Debranned MF and the flour with lipid removed, protein removed, or both lipid and protein removed (MF‐L‐P) were subjected to digestion assays. The in vitro starch digestibility and eGI of the millet samples and millet starch were compared with rice or wheat flour. Rapidly digestible starch, slowly digestible starch, and resistant starch (RS) of the samples were also calculated. Protease treatment and defatting resulted in significant reduction ( P < 0.05) in protein and lipid contents of samples. Significant increases in the in vitro starch digestibility and eGI of samples were observed after removal of protein, lipid, or both. The effect of lipid removal on in vitro starch digestibility of kodo millet was found to be more significant, compared with when proteins were removed. The eGI increased from 49.4 for cooked MF to 62.5 for MF‐L‐P. The eGI of cooked kodo millet starch was significantly lower than that of cooked rice flour. The RS (1.61%) of cooked rice was the least among the samples. The in vitro starch digestibility and eGI of rice were significantly higher than those of MF. Processes applied to kodo millet, such as decortication, that result in the removal of proteins, lipids, or both (especially lipids) would result in an increase in its in vitro starch digestibility and eGI. We therefore advocate for the development of acceptable products from whole millets to maintain its hypoglycemic property.